Research on Meeting the Demand of the Population for A Group of Medicines Intended for the Treatment of Skin Diseases - Sergeevich Streltsov, Evgeny (2021)
The problem of the spread of skin diseases in Russia and abroad in the last period is quite acute. Among the reasons for the development of this group of diseases, researchers determine genetic factors, poor ecology, impaired liver function, etc. In this regard, those suffering from this group of diseases are necessarily provided with qualified medical care, and pharmacy institutions form the necessary range of drugs that can improve the standard of living of patients. For this reason, we consider it necessary to analyze the level of demand for certain drugs used for the treatment of skin diseases in the pharmacy network of Belgorod, as well as factors that allow us to assess certain aspects that affect the formation of the range of these drugs in pharmacies. The purpose of the work was defined as follows: to conduct a study of meeting the demand of the population for groups of medicines intended for the treatment of skin diseases. The conducted analysis shows the following. Drugs intended for the treatment of skin diseases are in high demand (59.09%); 22.73% of drugs are in low demand, the lack of demand was observed in 18.18% of the studied group of drugs. In this paper, recommendations were formulated to optimize the assortment policy of the World of Medicines pharmacy chain in Belgorod. Since it was determined that high demand drugs such as Argosulfan, Belosalic, Avekort, Cinocap, Candiderm, Alorom, Lomaherpan, Metrogyl, Nitrofungin. It is for this reason that it is necessary to increase the volume of their purchases to better meet the demand of the population for these drugs. It was also revealed that it is necessary to reduce the volume of purchases of drugs, the demand for which is reduced. It is drugs such as Daktarin, Adolen, Camadol, Ammifurin, Bramisil, Batrafen, Berestin, Hiporhamin (they came in the results of ABC-analysis to the group C). In addition, the pharmacy should promote this group of drugs to familiarize consumers with them and offer them at a reduced price, so as not to burden the turnover of medicines and not to reduce the effectiveness of the pharmacy. The paper concluded that, according to the study, the demand for medicines used in the treatment of skin diseases is quite high. At the same time, the administration of the pharmacy chain should pay more attention to the analysis of the purchased groups of medicines in this category in order to prevent overloading the pharmacy balance with drugs, the demand for which is reduced, as this negatively affects the effectiveness of the pharmacy organization. In this regard, it is advisable to conduct an ABC analysis of the assortment groups of drugs at least once a quarter, as well as take the necessary measures to promote drugs used in the treatment of skin diseases that are in insufficient demand among the population.